India and the Islamic heartlands an eighteenth-century world of circulation and exchange - Sood, Gagan 1976- (Cambridge University Press, 2016)
Based on the chance survival of a remarkable cache of documents, India and the Islamic Heartlands recaptures a vanished and forgotten world from the eighteenth century spanning much of today's Middle East and South Asia. Gagan Sood focuses on ordinary people...traders, pilgrims, bankers, clerics, brokers, scribes, among others...who were engaged in activities marked by large distances and long silences. By elucidating their everyday lives in a range of settings, from the family household to the polity at large, Sood pieces together the connective tissue of a world that lay beyond the sovereign purview. Recapturing this obscured and neglected world helps us better understand the region during a pivotal moment in its history, and offers new answers to old questions concerning early modern Eurasia and its transition to colonialism.